Biosorption of Lead (II) onto soda lignin gels extracted from Nypa fruiticans. Issue 3 (June 2017) - Ogunsile, B.O.; Bamgboye, M.O.
Graphical abstract: Abstract: Lignin is relatively abundant in nature but its utilization potentials as an adsorbent for the removal of metals from waste water have not been fully exploited. Biosorption experiments were carried out for the removal of Pb +2 from aqueous solution, using novel lignin gels (soda lignin and sulfonated resinified soda lignin) extracted from Nypa fruitcans . The effects of major variables governing the efficiency of the process such as pH, adsorbent dosage, contact time, initial concentration and temperature were studied by the batch process. Equilibrium data was fitted into the Langmuir and Frendlich isotherm models. Adsorption kinetics was analyzed using the pseudo- first and second- order models while thermodynamic parameters such as ΔH, ΔS and ΔG were estimated accordingly. The results showed that the sorption process was best represented by the Langmuir isotherm while the pseudo- second- order model was the appropriate model describing the adsorption kinetics. The optimum adsorption occur at pH of 4 and 6, corresponding to a maximum adsorption of 94.24 and 96.34% for the unmodified lignin (UL), and sulfonated resinified lignin (SRL), respectively. The adsorption process was found to be endothermic and spontaneous. An indication of kinetic performance (Rw ), suggests that sulfonated lignin approaches equilibrium faster and would likely remove more Pb +2 from solution than the unmodified lignin. Similarly, optimization of the biosorbent dosage in a single stage batch design revealed that more than twice, the amount of SRL biosorbent is required by the UL to remove over 94% of lead (II) ions from aqueous solution.